Associations between digital technology and substance use among U.S. adolescents: Results from the 2018 Monitoring the Future survey. (1st August 2020) - Kaur, Navdep; Rutherford, Caroline G.; Martins, Silvia S.; Keyes, Katherine M.
Highlights: Social media and digital technology exposes youth to substance-related content. Adolescents who use social media are more likely to use substances. This relationship is also observed across other forms of digital communication. More socially connected adolescents are more likely to use substances. Abstract: Objective: Social media and other digital technology use facilitate connection among adolescents, but also may reinforce norms and substance-related content from peers and advertisers. We use nationally representative data to examine the association between digital technology and past 30-day use of alcohol, cannabis, and vaping. Methods: Data were drawn from the 2018 Monitoring the Future survey of US adolescents (N = 44, 482). Poisson regressions estimated the association between hours/day of technology use and past 30-day use of alcohol, cannabis, and vaping adjusting for grade, sociodemographics, and other past-year drug use. Results: Across grades, mean hours of social media/day was 3.06 (standard deviation = 2.90), past 30-day alcohol, cannabis, flavor vaping, cannabis vaping, and nicotine vaping were 15.7 %, 12.6 %, 10.6 %, 4.9 %, and 11.2 %, respectively. Digital technology use that required interaction with others was associated with increased risk of past 30-day drinking, cannabis use, and vaping. For example, social media 3+ hours/day was associated with past 30-day drinking (adjusted relative risk [aRR]: 1.99, 95 % CI: 1.65, 2.41). The magnitude of association was consistent across texting, phone calls, and video chatting, which were all more strongly associated with substance use than with activities that do not require interaction such as gaming and watching videos. Conclusion: Digital technology that facilitates interaction among adolescents, such as texting and social media, is associated with past substance use. Magnitudes of association are consistent across substances, supporting the hypothesis that networks of adolescents are social drivers of substance use, rather than the technology itself.